An unexpected presentation of very severe hypertriglyceridemia in a boy with Coffin-Lowry syndrome : a case report - Tan, Sue Lyn; Muhammad Ghazali, Ahmad Narihan; Koa, Ai Jiun (Springer Nature, 2023)
Background Coffin-Lowry syndrome (CLS) is a rare X-linked condition with intellectual disability, growth retardation, characteristic facies and skeletal anomalies. To date, hypertriglyceridemia has not been reported in literature to be associated with CLS.